(untitled) (International Journal of Ayurveda and Pharma Research, 2024)
Duchenne muscular dystrophy is a neuromuscular disease. This is an X-linked recessive disease caused by mutations in the dystrophin protein gene located on the short arm of the X chromosome, in the Xp21 region. It causes progressive muscle weakness due to wasting of muscle fibers. It causes loss of ability to stand, walk, and move before age 10; most patients die in their 20s. Since there is no specific treatment in any medical system and the prognosis of the disease is uncertain, if we start treatment at an early stage, children with DMD can walk, it can slow or stop progressive muscle degeneration. DMD cannot be directly related to a single disease in Ayurveda. Most major neuromuscular disorders are determined by Vata dosha. In Ayurveda, this pathogenesis can be clearly understood by the concept of Adibala Pravrutta Vyadhi (genetic disease). Here the pathogenesis is due to Beeja Bhagavayava Dusti (partial chromosomal defect) leading to Mamsa Vata Dushti.